Analisis Efektivitas Penyaluran Pembiayaan Murabahah Terhadap Pertumbuhan Laba Bersih : Studi Kasus: Bank BJB Syariah KCP Lippo Cikarang - Ang Riqko Suhendi; Mia Lasmi Wardiyah (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
This study aims to analyze the effectiveness of murabahah financing distribution on net profit growth at Bank BJB Syariah Lippo Cikarang Branch Office (KCP). The method used in this study is a descriptive qualitative method with a case study approach. Data were obtained through in-depth interviews with internal bank parties, direct observation, and documentation of financial reports and murabahah financing data from previous years. The results of the study indicate that murabahah financing distribution at Bank BJB Syariah KCP Lippo Cikarang has a significant contribution to increasing net profit, especially because of the characteristics of murabahah which provides a fixed profit margin for the bank. However, financing effectiveness is also influenced by external factors such as macroeconomic conditions, people's purchasing power, and the bank's ability to analyze financing risks. Overall, the strategy of murabahah financing distribution that is right on target and good risk management has been proven to be able to increase bank profitability. This study is expected to be a reference for management in improving the quality of financing distribution and financial management based on sharia principles.